Planned Retirement Timing in Europe: Are Europeans Adapting to the Policy of Extending Working Lives - Hess, Moritz; Naegele, Laura; Becker, Lena; Mäcken, Jana; De Tavernier, Wouter (Frontiers in Sociology, 2021)
As populations are ageing concerns regarding the sustainability of European welfare states have come to the forefront. In reaction, policy makers have implemented measurements aimed at the prolongation of working lives. This study investigates weather older workers have adapted their planned retirement age, as a result of this new policy credo. Based on data from Survey of Health, Ageing and Retirement in Europe (SHARE) the analysis shows an increase of the planned retirement age (1.36 years) across all ten European countries investigated, albeit with country-specific variations. Variations on the individual level can be detected in regard to gender, education and self-reported health status.